Tele-ophthalmology versus Traditional Fundus Photography for Diabetic Retinopathy Screening: A Comparative Meta-analysis of Diagnostic Accuracy, Cost-Effectiveness, and Health Policy Uptake - Ramzi Amin; Dio Asgira Rizky (Community Medicine and Education Journal, 2024)
Diabetic retinopathy (DR) remains a leading cause of preventable blindness globally, imposing a significant public health burden. Effective screening is paramount for early detection and timely intervention. Traditional fundus photography (TFP), often requiring specialized equipment and personnel, faces access challenges. Tele-ophthalmology (TO) has emerged as a potential solution to improve screening coverage. However, rigorous comparative evidence regarding its diagnostic accuracy relative to established TFP methods, its economic viability, and factors influencing its adoption into health policy and routine practice remains fragmented. This systematic review and meta-analysis aimed to synthesize the evidence comparing TO and TFP for DR screening across these critical domains. We conducted a systematic literature search adhering to PRISMA guidelines across PubMed, EMBASE, and Web of Science databases for studies published between January 1st, 2013, and December 31st, 2023. Keywords included "diabetic retinopathy," "screening," "teleophthalmology," "telemedicine," "fundus photography," "digital imaging," "diagnostic accuracy," "cost-effectiveness," and "policy." Inclusion criteria mandated studies directly comparing TO (any modality involving remote image grading) with TFP (in-person acquisition and grading or local grading) for detecting any DR or referable DR (RDR) in diabetic populations. Outcomes of interest were diagnostic accuracy (sensitivity, specificity), cost-effectiveness metrics (e.g., ICER), and reported health policy uptake or implementation factors. Study quality was assessed using adapted QUADAS-2 criteria for accuracy studies and relevant checklists for economic evaluations. 6 studies met the full inclusion criteria for this meta-analysis. Pooled sensitivity for detecting RDR using TO was 0.90 (95% CI: 0.87-0.93), compared to 0.92 (95% CI: 0.89-0.95) for TFP. Pooled specificity for TO was 0.91 (95% CI: 0.88-0.94) versus 0.93 (95% CI: 0.90-0.95) for TFP. Moderate heterogeneity was observed (I² > 50%). Health policy uptake varied significantly, influenced by factors such as established reimbursement frameworks, governmental support, integration with electronic health records, availability of trained non-ophthalmic personnel, and robust quality assurance protocols. In conclusion, tele-ophthalmology demonstrates high diagnostic accuracy for DR screening, comparable, albeit potentially slightly lower on average, to traditional fundus photography. Economic evaluations largely favor TO, suggesting significant potential for efficient resource allocation in DR screening programs. However, successful translation into widespread, effective public health policy requires addressing implementation barriers related to infrastructure, workforce training, reimbursement parity, and quality assurance.